Pengaruh Modul Ajar Kurikulum Merdeka terhadap Peningkatan Profil Pelajar Pancasila - Setiawan, Angga; Nugroho, Wahyu; Puspasari, Yovita (Teaching, Learning, and Development, 2024)
Abstract: Education is a tool in the intellectual life of the nation. Education is very important to prepare the future of the younger generation. Through education, a person, especially students, has the opportunity to gain learning experiences that are very useful for their lives. The problem in an education is the change from the old curriculum to the new curriculum and the existence of a new teaching module. The teaching modules in the Independent Curriculum are learning tools prepared by the teacher to plan the learning process. Interestingly, the problem is that the author wants to know whether there is an influence of the independent curriculum teaching module on increasing the profile of Pancasila students. To get an overview and maximum research results, the authors conducted research on 4th grade students at SD Negeri 2 Sengon with a population of 12 students. The data analysis method uses the Paired Simple T-Test. Based on the results of data analysis, it is known that the total pretest score of class 4 students is 733 with an average of 61.08, the highest score is 70 and the lowest score is 40. Meanwhile, the total post-test score is 927 with an average of 77.25 with the highest score of 90 and the lowest score is 65 and with the paired sample t-test on the profile of Pancasila students in grade 4 students, it shows that the significance value is 0.000 where p less than 0.05 which means H0 is rejected. Thus it can be concluded that there is an influence of the independent curriculum teaching module on the profile of Pancasila students participating 4th grade at SDN 2 Sengon. Abstrak: Pendidikan merupakan suatu sarana dalam mencerdaskan kehidupan bangsa. Pendidikan sangat penting guna mempersiapkan masa depan generasi muda. Melalui pendidikan, seseorang khususnya peserta didik mempunyai peluang untuk mendapatkan pengalaman belajar yang sangat berguna bagi kehidupannya. Masalah dalam sebuah pendidikan adalah pergantian dari kurikulum lama ke kurikulum baru dan adanya sebuah modul ajar baru. Modul ajar dalam Kurikulum Merdeka merupakan perangkat pembelajaran yang disusun oleh guru untuk merencanakan proses pembelajaran. Menariknya permasalahan tersebut penulis ingin mengetahui ada tidaknya pengaruh modul ajar kurikulum merdeka terhadap peningkatan profil pelajar pancasila. Untuk mendapatkan gambaran dan hasil penelitian yang maksimal penulis melakukan penelitian pada peserta didik kelas 4 di SD Negeri 2 Sengon dengan populasi yang berjumlah 12 peserta didik. Metode analisis data menggunakan Paired Simple T-Test. Berdasarkan hasil analisis data diketahui total nilai pretest peserta didik kelas 4 adalah 733 dengan rata-rata 61,08 nilai tertinggi 70 dan nilai terendah 40. Sedangkan total nilai post test adalah 927 dengan rata-rata 77,25 dengan nilai tertinggi 90 dan nilai terendah adalah 65 dan dengan uji paired sample t-test terhadap profil pelajar pancasila peserta didik kelas 4, menunjukkan bahwa nilai signifikansinya adalah 0,000 dimana p kurang dari 0,05 yang artinya H0 ditolak dengan demikian dapat disimpulkan terdapat pengaruh modul ajar kurikulum merdeka terhadap profil pelajar pancasila peserta didik kelas 4 di SDN 2 Sengon.